SPSS 16 Made Simple - Paul R. Kinnear (Warner Books, 2008)
The book provides guidance on the choice of statistical techniques and advice on how to report the results of statistical analysis. The first chapter sets the scene with a survey of typical research situations, key terms and advice on the choice of statistical techniques. It also provides clear signposts to where each technique can be found in the body of the book. The next chapter introduce the reader of the use of SPSS 16, showing how to enter and describe a data set both statistically and graphically, using the powerfull capabilities of the chart builder. Each of the remaining chapters concentrates on one particular kind of research situation and the appropriate statistical techniques. In summary, SPSS 16 Made simple: Gets you started with SPSS 16, Shows you how to run an exploratory data analysis (EDA) using SPSS's extensive graphics and data -handling menus. Reviews the elements of statistical inference. Helps you to choose appropriate statistical techniques. Warns you of the pitfalls arising from the the misuse of statistics. Shows you how to report the results of a statistical analysis. Shows you how to use syntax to implement some useful procedures and operations. Has a comprehensive index, which allows you to find a topic by several different routes. Has a comprehensive glossary.